The problem is to prove, by induction, that \(\displaystyle \sum_{k= 1}^n (-1)^{n- k}k^2= \frac{n(n+1)}{2}\).
You say "now there is both n and k on the left side". I presume you mean the n in "\(\displaystyle (-1)^{n- k}\)" not the sum "to n" since that is commonly there. Surely you know, by simple algebra, that \(\displaystyle (-1)^{n-k}= (-1)^n(-1)^{-k}\) and then we can factor \(\displaystyle (-1)^n\) out of the sum. Further, since \(\displaystyle \frac{1}{-1}= -1\), \(\displaystyle (-1)^{-k}= (-1)^k\).
The problem is to prove, by induction, that \(\displaystyle (-1)^n\sum_{k= 1}^n (-1)^k k^2= \frac{n(n+1)}{2}\).
Now, induction should be obvious. The "base case" is n= 1 and in that case, the left side is just \(\displaystyle (-1)(-1)(1^2)= 1\) and the right side is \(\displaystyle \frac{1(1+1)}{2}= 1\).
Since this is a sum, the "n+1" case is just the sum up to n, the "n" case with one additional term:
\(\displaystyle (-1)^n\sum_{k=1}^n (-1)^k k^2+ (-1)^{n+1}(-1)^{n+1} (n+1)^2\)
Since the "induction hypothesis" is that the sum in that last is \(\displaystyle \frac{n(n+1)}{2}\), this reduce to showing that \(\displaystyle \frac{n(n+1)}{2}+ (n+1)^2= \frac{(n+1)(n+2)}{2}\).
(I have used the obvious fact that \(\displaystyle (-1)^{n+1}(-1)^{n+1}= 1\).)